(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article provides a comprehensive analysis of the history of the study of the periodical press of the Surkhandarya region. It covers the formation, stages of development of periodicals in the region, their role and significance in the life of society. It also deeply studies the processes of scientific research of the Surkhandarya press, research conducted in this regard, published works and existing problems. The article also considers the scientists who contributed to the study of the periodical press and their scientific heritage, which serves as the basis for future research.